Foreign Science of Administrative Law and Possible Areas of Its Adaptation in Ukraine - Haran, Olha Volodymyrivna; Maksimentseva, Nadiia; Кhrystynchenko, Nadiia; Povydysh, Vladyslav Volodymyrovych (Jurnal Cita Hukum, 2020)
AbstractThe purpose of the article is to study the foreign science of administrative law and to determine certain areas of its adaptation in Ukraine. To achieve this purpose, we have used such methods of scientific cognition as dialectical, historical, formal and logical, system, and structural. The authors of the article have studied the content and specific features of foreign administrative and legal science, as well as have suggested possible ways to implement it into the scientific and legal system of Ukraine. It has been stated that the effective development of the national system of public administration is impossible without the quality functioning of science, which deals with studying forms and methods of administration, and an effective management system is essential for the success of any country. It has been noted that to achieve high results in the work of state agencies, their staff must be well educated on the use of optimal forms and methods of administration activity. Professionals who represent the state or local self-governments while performing their professional duties must have all the necessary skills (means) to achieve the tactical and strategic objectives set before them. The leadership of such agencies must be able to think globally and be able to set specific and objective tasks, as well as to provide the most effective means for their implementation. The historical aspects of the formation and development of administrative and legal science as a key element of the administrative system in different countries have been studied.Keywords: Administrative Law, Legal Regulation, Administrative, and Legal Science, Administrative Activity, Legislative Provision. Abstrak:Tujuan artikel ini adalah untuk mempelajari ilmu asing dari hukum administrasi dan untuk menentukan area tertentu dari adaptasinya di Ukraina. Untuk mencapai tujuan ini, penulis menggunakan metode kognisi ilmiah seperti dialektis, historis, formal dan logis, sistem, dan struktural. Penulis artikel telah mempelajari konten dan fitur khusus dari ilmu hukum dan administrasi asing, serta telah menyarankan cara yang mungkin untuk diterapkan ke dalam sistem ilmiah dan hukum Ukraina. Telah dinyatakan bahwa pengembangan yang efektif dari sistem administrasi publik nasional tidak mungkin tanpa fungsi ilmu pengetahuan yang berkualitas, yang berkaitan dengan mempelajari bentuk dan metode administrasi, dan sistem manajemen yang efektif sangat penting untuk keberhasilan negara manapun. Perlu dicatat bahwa untuk mencapai hasil yang tinggi dalam pekerjaan lembaga negara, staf harus dididik dengan baik tentang penggunaan bentuk dan metode kegiatan administrasi yang optimal. Profesional yang mewakili pemerintah sendiri negara bagian atau lokal saat menjalankan tugas profesional mereka harus memiliki semua keterampilan (sarana) yang diperlukan untuk mencapai tujuan taktis dan strategis yang ditetapkan sebelumnya. Pimpinan lembaga tersebut harus mampu berpikir secara global dan dapat menetapkan tugas yang spesifik dan obyektif, serta menyediakan sarana yang paling efektif untuk pelaksanaannya. Aspek historis pembentukan dan perkembangan ilmu administrasi dan hukum sebagai elemen kunci dari sistem administrasi di berbagai negara telah dipelajari.Kata Kunci: Hukum Administrasi, Peraturan Hukum, Tata Usaha, dan Ilmu Hukum, Kegiatan Administrasi, Ketentuan Legislatif. АннотацияЦелью статьи является изучение зарубежной науки административного права и определение направлений ее адаптации в Украине. Для достижения поставленной цели использованы следующие методы научного познания: диалектический, исторический, формально-логический и системно-структурный. В статье исследуется содержание и особенности зарубежной науки административного права, а также предлагаются возможные пути ее внедрения в научно-юридическую систему Украины. Указывается, что развитие отечественной системы публичного управления невозможно без качественного функционирования науки, занимающейся изучением форм и методов администрирования, а действенная управленческая система является крайне необходимым для успешной жизнедеятельности любой страны. Отмечается, что для достижения высоких результатов в работе государственных органов их кадровый состав должен быть хорошо образованным по вопросам использования оптимальных форм и методов управленческой деятельности. Специалисты, которые во время выполнения своих профессиональных обязанностей представляют государство или органы местного самоуправления, должны обладать всеми необходимыми навыками (средствами) для достижения поставленных перед ними тактических и стратегических задач. Руководство таких органов должно быть способным к глобальному мышления и уметь ставить конкретные и объективные задачи, а также предоставлять для их выполнения наиболее эффективные средства.Ключевые слова: Административное право, Правовое регулирование, Наука административного права, Управленческая деятельность, Законодательное обеспечение.